PETROCHEMICAL AND MINERALOGICAL CONSTRAINTS FOR DIAGNOSTICS OF YAKUTIAN KIMBERLITES - Golubeva Yu.Yu.; Tsepin A.I. (My University, 2004)
Typomorphic minerals were studied in order to refine the nomenclature of alkaline ultramafic rocks. These are micas and perovskites. We compared chemical compositions of micas from typical kimberlites, such as the Udachnaya pipe (Daldyn field), Malyi Kounamka pipe (Kuranakh field), Nebaibyt pipe )Srednii Kounamka field), and Bazovaya 2 and Billyakh 4 pipes (Kharamai field), with those from aforementioned objects, which, geochemically, approximate orangeites and lamproites.